Pengaruh E-learning, Knowledge Sharing, dan Job Rotation Terhadap Kinerja Karyawan dengan Pengembangan Diri sebagai Variabel Intervening [Studi pada Generasi Z di Kota Semarang] - Prasetyo, Ramadhan; Hawik Ervina Indiworo; Ratih Hesty Utami Puspitasari (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The study aims to analyze the effect of e-learning, knowledge sharing and job rotation on the performance of generation Z employees in Semarang City mediated by self-development. This research is quantitative type using PLS-SEM data analysis technique with SmartPLS 3.2.9 software. The results of this study prove that: (1) E-learning affects employee performance; (2) Knowledge sharing has no effect on employee performance; (3) Job rotation has no effect on employee performance; (4) Self-development affects employee performance; (5) E-learning affects self-development; (6) Knowledge sharing has no effect on self-development; (7) Job rotation affects self-development; (8) Self-development mediates e-learning on employee performance; (9) Self-development does not mediate knowledge sharing on employee performance; (10) Self-development does not mediate job rotation on employee performance.